Novi pristupi izdavaštvu na Univerzitetu u Sarajevu / New Approaches to University of Sarajevo's Publishing Activities (Pregled: časopis za društvena pitanja / Periodical for social issues, 2022)
This text is a review of New Approaches to University of Sarajevo's Publishing Activities.